2018
DOI: 10.1111/bph.14348
|View full text |Cite
|
Sign up to set email alerts
|

The opioid oxycodone use‐dependently inhibits the cardiac sodium channel NaV1.5

Abstract: Oxycodone leads to an accumulation of Na 1.5 channels in inactivated states, with a slow time course. Although the concentrations needed to elicit cardiac arrhythmias in vitro are relatively high, some patients under long-term treatment with oxycodone as well as drug abusers and addicts might suffer from severe cardiac side effects induced by the slowly developing effects of oxycodone on Na 1.5 channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Due to the difficulty in developing isoform-specific Na v channel blockers, newly developed, relatively non-specific, voltage-gated sodium channel blockers often cause adverse effects in patients ( Mulroy, 2002 ; de Lera Ruiz and Kraus, 2015 ; Dokken and Fairley, 2021 ). Because some opioid analogs such as fentanyl, oxycodone, buprenorphine, meperidine, and loperamide block sodium channels ( Wagner et al ., 1999 ; Olschewski et al ., 2001 ; Wolff et al ., 2004 ; Haeseler et al ., 2006 ; Leffler et al ., 2012 ; Wu et al ., 2017 ; Meents et al ., 2018 ), we aimed to determine whether tramadol also blocks sodium channels.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the difficulty in developing isoform-specific Na v channel blockers, newly developed, relatively non-specific, voltage-gated sodium channel blockers often cause adverse effects in patients ( Mulroy, 2002 ; de Lera Ruiz and Kraus, 2015 ; Dokken and Fairley, 2021 ). Because some opioid analogs such as fentanyl, oxycodone, buprenorphine, meperidine, and loperamide block sodium channels ( Wagner et al ., 1999 ; Olschewski et al ., 2001 ; Wolff et al ., 2004 ; Haeseler et al ., 2006 ; Leffler et al ., 2012 ; Wu et al ., 2017 ; Meents et al ., 2018 ), we aimed to determine whether tramadol also blocks sodium channels.…”
Section: Discussionmentioning
confidence: 99%
“…If with six groups (f = 0.4, α = 0.05, power = 0.7, N = 12 per group). We referred to the calculated results from this analysis and other studies with similar investigations (Cox et al, 2006;Estacion et al, 2008;Meents et al, 2018). Studies were designed to generate groups of equal size.…”
Section: Data and Statistical Analysismentioning
confidence: 99%
“…For estimation of the number of cells needed per experiment, we performed an a priori analysis for experiments where two groupsassuming normal distribution-were compared (d = 0.8, α = 0.05, power = 0.7, N = 21 per group), for experiments with three groups (f = 0.4, α = 0.05, power = 0.7, N = 18 per group), and for experiments with six groups (f = 0.4, α = 0.05, power = 0.7, N = 12 per group). We referred to the calculated results from this analysis and other studies with similar investigations (Cox et al, 2006;Estacion et al, 2008;Meents et al, 2018). Studies were designed to generate groups of equal size.…”
Section: Data and Statistical Analysismentioning
confidence: 99%
“…The current research focuses on hERG channels, which affect the QT interval most significantly. Recent studies have also identified new mechanisms and ion channel loci, I K1 for example [ 16 , 17 , 47 ].…”
Section: Opioids and Ion Channelmentioning
confidence: 99%